2013
DOI: 10.2214/ajr.12.9667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and Simulated Reduced–Tube Current MDCT for Evaluation of Suspected Appendicitis in the Pediatric Population

Abstract: OBJECTIVE The purpose of this study was to compare CT with conventional and simulated reduced–tube current in the evaluation for acute appendicitis in children. MATERIALS AND METHODS Validated noise-addition (tube current–reduction) software was used to create 50% and 75% tube current reductions in 60 CT examinations performed for suspected appendicitis, resulting in 180 image sets. Three blinded pediatric radiologists scored the randomized studies for the following factors: presence of the normal appendix o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The dose-simulation technique, which simulates dose reduction at multiple levels with a single scan, can be a more favorable methodology free of clinical and ethical concerns. This technique has been introduced for a systematic exploration of reduced dose levels [43,44], but it has not yet been studied in conjunction with IR in clinical research. While we tested 2-mSv appendiceal CT and showed that IR did not exhibit any diagnostic advantage over FBP, our results can justify future studies exploring an even more dramatically reduced dose level (e.g., 1 mSv or sub-mSv) at which IR might truly benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The dose-simulation technique, which simulates dose reduction at multiple levels with a single scan, can be a more favorable methodology free of clinical and ethical concerns. This technique has been introduced for a systematic exploration of reduced dose levels [43,44], but it has not yet been studied in conjunction with IR in clinical research. While we tested 2-mSv appendiceal CT and showed that IR did not exhibit any diagnostic advantage over FBP, our results can justify future studies exploring an even more dramatically reduced dose level (e.g., 1 mSv or sub-mSv) at which IR might truly benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The development of noise addition paradigms and lesion insertion tools have allowed for investigations that use one set of patient scans to create multiple simulated data sets without additional radiation exposure (11). A validated lesion insertion software tool found that observers could not readily distinguish real liver lesions from simulated anthropomorphic liver lesions (12).…”
mentioning
confidence: 99%
“…Although the primary outcome measure for dose reduction investigations is reader accuracy (11,13), other factors play into the clinical applications. For example, confidence levels and examination review times may relate to fatigue but do not necessarily affect performance.…”
mentioning
confidence: 99%